Potential Biochemical Markers Affecting Aging and “the Compensatory Effects” of Canola (Brassica napus L.) Seeds Stored in Deep Underground - Jingchen Wang; Bo Tan; Yuxin He; Chao Liu; Naiwen Li; Xiao Tan; Heng Lu (Agriculture, 2023)
Understanding the impact of deep underground environment on seed storage is an essential prerequisite for realizing the idea of “deep underground agriculture”. To explain the changes in seed germination performance after deep underground storage, we examined the biochemical properties of envelope-packed canola seeds stored for three different durations (66, 90, and 227 days) in four different depths (0, 240, 690, and 1410 m) of a gold mine. Results showed that deep underground storage duration was the leading cause of biochemical properties changes of canola seed, while storage depth exacerbated such changes. Deep underground environment significantly suppressed seed superoxide dismutase (SOD) and soluble sugar (SS), which could be the main reason for the accelerated loss of seed vigor. The appearance of the “compensatory effect” was mainly attributed to the increase in seed growth hormone and the decrease in abscisic acid (ABA) content. The most significant enhancement in growth hormone content was observed in seeds stored at a depth of 1410 m for 66 days, where indoleacetic acid (IAA), gibberellin (GA), and cytokinin (CTK) increased by 63.37%, 21.77%, and 79.36%, respectively. In this study, short-term deep underground storage could enhance seedling growth, but the recommended storage duration for canola seeds should not be longer than 90 days.